The geography of lifestyle center growth: The emergence of a retail cluster format in the United States. (March 2022) - Rice, Murray; Sorenson, Matthew; Aversa, Joseph
Abstract: Just as geographers have given much attention to the evolution of shopping malls and power center retail complexes, it is equally important for research in business geography to continue to provide developmental evidence as new and distinctive retail cluster formats emerge and grow. The lifestyle center is a unique type of retail complex that has experienced much expansion across the United States yet has not received much research attention from location researchers. This study provides answers to basic questions, including the geography of lifestyle center development, the relationship of lifestyle center development to traditional mall activity, and the characteristics of lifestyle center market areas in comparison with the trade areas of their mall counterparts. The results show that lifestyle centers are developing in distinctive locations and markets within American cities that are not well-served by traditional malls. The study results also establish that lifestyle centers have a significant bias toward location in large cities, representing a clear contrast with traditional malls and their locational orientation toward smaller centers. The study summarizes these findings and argues that the emergence of the lifestyle center format has important implications for retailers, commercial property developers, and local economic development officials.